2023
DOI: 10.2196/39992
|View full text |Cite
|
Sign up to set email alerts
|

Regional Difference in the Impact of COVID-19 Pandemic on Domain-Specific Physical Activity, Sedentary Behavior, Sleeping Time, and Step Count: Web-Based Cross-sectional Nationwide Survey and Accelerometer-Based Observational Study

Abstract: Background Physical activity (PA) and sedentary behavior (SB) have been affected by the COVID-19 pandemic and its restrictive environments, such as social distancing and lockdown measures. However, regional differences in the changes in domain-specific PA and SB in response to the COVID-19 pandemic are not clearly understood. Objective This study aimed to examine regional differences in domain-specific PA and SB, as well as sleeping time in response to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The detailed duration of observation for each study is shown in Table 1 . Nine studies measured daily steps with smartphones [ 19 , 37 , 40 , 41 , 43 , 45 , 46 , 50 , 54 ], 8 with wearable activity trackers [ 20 , 38 , 39 , 47 , 48 , 51 - 53 ], and 2 with both wearable activity trackers and smartphones [ 44 , 49 ]; 1 study did not specify the measurement device used in the survey [ 42 ]. One study provided 4 groups of data from 4 countries separately [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed duration of observation for each study is shown in Table 1 . Nine studies measured daily steps with smartphones [ 19 , 37 , 40 , 41 , 43 , 45 , 46 , 50 , 54 ], 8 with wearable activity trackers [ 20 , 38 , 39 , 47 , 48 , 51 - 53 ], and 2 with both wearable activity trackers and smartphones [ 44 , 49 ]; 1 study did not specify the measurement device used in the survey [ 42 ]. One study provided 4 groups of data from 4 countries separately [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 151 studies did not report relevant outcomes (ie, daily steps), 14 did not provide necessary data for meta-analysis, 13 focused on irrelevant populations, 5 were not observational studies, 3 were conducted with financial incentives, 2 reported duplicated data, and 1 was a conference abstract. The remaining 20 studies were included in the meta-analysis [19,20,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Figure 1 shows the PRISMA flow diagram.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using such a system, it is possible to assess the physical activity of a large number of people simultaneously and at the same time with high accuracy at low cost [17] and to assess each activity intensity (Figure 2) [18]. It is also possible to evaluate the physical activity of a large population with COVID-19 online, and the effects of COVID-19 on physical activity have been clarified [19,20]. The 24-hour activity recording method suggests the possibility of physical activity assessment by voice input (Figures 3 and 4) by introducing a voice recognition application programming interface (API) [21].…”
Section: Evaluation Of Physical Activity Using Ictmentioning
confidence: 99%
“…Previous research Vol.32, No. 4, November 2023: 419-427 has demonstrated the effectiveness of the socio-ecological model in identifying multiple factors influencing PA in COVID-19 pandemic [12][13][14]. For example, one study reported that high levels of social support were linked to a 64% increased likelihood of sustaining PA [12].…”
Section: Introductionmentioning
confidence: 99%